Penyembah-Penyembah Benar Menurut Yohanes 4:23: Kaitannya Terhadap Pengenalan Akan Allah - Didit Yuliantono Adi; Endik Firmansah (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
This scientific study aims to explore the meaning of true worship according to John 4:23 and its relation to knowing God. True worship must be grounded in the three essential aspects of the Christian faith: orthodoxy (right doctrine), orthopraxy (right practice), and ortholatry (right worship). The truth in this context is not philosophical or anthropocentric but Christocentric, with Scripture as its ultimate standard. God is both the foundation and the ultimate goal of all Christian reality. As the Creator, He sovereignly rules over all of life. He alone is worthy of worship and glorification. Scripture explicitly describes worshiping God as being conducted